Understanding the factors influencing healthcare providers' burnout during the outbreak of COVID-19 in Jordanian hospitals - Abdullah Algunmeeyn; Faris El-Dahiyat; Mohammad Mitib Altakhineh; Mohammad Azab; Zaheer- (Taylor & Francis Group, 2020)
Background Coronavirus disease (COVID-19) is an infectious disease caused by a newly discovered coronavirus. The nature of healthcare providers' occupation puts them at an increased risk of getting any contagious disease, including COVID-19. They are on the front line of the COVID-19 outbreak response and as such are at risk of contracting this virus. The infectious disease started from China in December 2019 and spread rapidly throughout countries, including Jordan. Especially, recent studies indicated that Jordanian healthcare providers' work conditions and demographic are significant factors for healthcare providers' burnout. Additionally, burnout has been increased among healthcare providers in Jordanian hospital. Aim The present investigation aims to better understand the factors affecting pharmacists', physicians', and nurses' burnout during the outbreak of COVID-19 to provide basic information for lowering and preventing the level of burnout in Jordanian hospitals. Method This study is qualitative in nature, adopting face-to-face interviews as the key instrument of data collection in one hospital in Jordan. The sample interviewed consisted of 30 healthcare providers in total (10 nurses, 10 physicians. and 10 pharmacists). Result Three key factors to healthcare providers' burnout were identified in the sampled hospitals: job stress, staff and resource adequacy, fear of COVID-19 infection, and interprofessional relationships in healthcare practice. The examination also offers recommendations for lowering and preventing healthcare providers' burnout in Jordanian hospitals. Conclusion This study explored the main factors of healthcare providers' burnout during the outbreak of COVID-19 in Jordanian hospitals, thereby making an original contribution to existing knowledge, as it is the first empirical exploration of healthcare providers' burnout during the outbreak of COVID-19. As such, it has attempted to offer an in-depth understanding of the factors impacting this issue.